ANALISIS PENGARUH MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN FOOD AND BAVERAGES YANG TERDAFTAR DI BEI TAHUN 2019-2022 - Khoirunnisa, Sabrina Aulia; Tantra, Arda Raditya; Ariani, Dewi (Universitas Ngudi Waluyo, 2024)
Developments in the business world in all sectors continue to experience competition,including Food and Baverages companies. The company continues to strive for workingcapital to obtain maximum profits. The aim of this research is to determine the effect ofworking capital as interpreted by cash turnover, accounts receivable turnover, inventoryturnover and total asset turnover on profitability. This research uses descriptivequantitative research methods with multiple linear regression analysis. The data used inthe research is secondary data in the form of company financial reports. The populationin this study were all companies in the Food and Baverages sector listed on the IndonesiaStock Exchange (BEI) from 2019 - 2022, where there were 28 companies so that 112 datawere collected. The sample used in this research used a purposive sampling method whichwas based on considering the value of ROA positive, so that 93 data were obtained whichwere used as research samples. The results of this research indicate that cash turnoverhas a positive effect on profitability. Receivables turnover has a negative effect onprofitability. Inventory turnover has a positive effect on profitability. Total asset turnoverhas no effect on profitability.